ПРИМЕНЕНИЕ НАНОСТРУКТУРИРОВАННЫХ УГЛЕРОДНЫХ АДСОРБЕНТОВ ДЛЯ ВЫДЕЛЕНИЯ БИОМОЛЕКУЛ И ЛЕКАРСТВЕННЫХ РАСТИТЕЛЬНЫХ СУБСТАНЦИЙ (Experimental biology, 2017)
The results of physico-chemical studies on locally produced nanostructured carbon materials are reported in this paper. Microporous-mesoporous carbonaceous adsorbents were obtained and tested for chromatographic separation of molecular sieve markers. The results suggest the applicability of carbon nanosorbents for both separation and isolation of a protein-lipid complex, as well as medicinal herbal substances.
Keywords: carbon materials; protein-lipid complex